#TITLE_ALTERNATIVE# - REZA RINALDY (NIM: 13204048), MUHAMMAD
In this report virtual LC filter acting as additional controller in dc-dc converter to reduce the low-frequency output current ripple is presented. Virtual LC filter has the same function like the one of passive LC filter connected in series to the output side of the converter. Virtual LC filter has a resonance frequency which can be tuned to a certain frequency. In this research filter is tuned to a certain resonance frequency which is the same with the frequency of output current ripple. Besides, this filter can be designed in such a way so that it only affects the output current ripple without affecting system response in respect to the reference. Hence, virtual LC filter can be designed separately from the existing controller without affecting the performance of the controller. Simulation and experimental results are shown to verify the performance of the proposed virtual LC filter in reducing the converter's low-frequency output current ripple.